Meta-Analysis of the Validity of General Mental Ability for Five Performance Criteria: Hunter and Hunter (1984) Revisited - Salgado, Jesús F.; Moscoso, Silvia (Frontiers in Psychology, 2019)
This paper presents a series of meta-analyses of the validity of general mental ability (GMA) for predicting five occupational criteria, including supervisory ratings of job performance, production records, work sample tests, instructor ratings, and grades. The meta-analyses were conducted with a large database of 467 technical reports of the validity of the General Aptitude Test Battery (GATB) which included 630 independent samples. GMA showed to be a consistent predictor of the five criteria, but the magnitude of the operational validity was not the same across the five criteria. Results also showed that job complexity is a moderator of the GMA validity for the performance criteria. We also found that the GMA validity estimates are slightly smaller than the previous ones obtained by Hunter (1983a; Hunter & Hunter, 1984). Finally, we discuss the implications of these findings for the research and practice of personnel selection.